Two cases of first onset intrahepatic cholestasis of pregnancy associated with moderate ovarian hyperstimulation syndrome after IVF treatment and review of the literature. (4th July 2017) - Mutlu, Mehmet Firat; Aslan, Koray; Guler, Ismail; Mutlu, Ilknur; Erdem, Mehmet; Bozkurt, Nuray; Erdem, Ahmet
Abstract: Intrahepatic cholestasis of pregnancy (ICP) is an uncommon disorder, which generally occurs in the second and third trimester of pregnancy with symptoms of pruritus. The cause of ICP is unknown but genetic, hormonal and environmental factors contribute to its pathogenesis. The aetiology of ICP is unclear but elevation in oestrogen levels thought to cause ICP is typically seen in the third trimester of pregnancy, and for this reason it is not usually considered in the differential diagnosis of pruritus and liver function disorders in the first trimester of the pregnancy. We present two cases of pregnancy after IVF treatment diagnosed with ICP following the development of OHSS, deteriorating liver function tests and severe pruritus.